2007
DOI: 10.1128/mcb.00500-07
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Turnover and Translation Regulatory RNA-Binding Protein Expression through Binding to Cognate mRNAs

Abstract: RNA-binding proteins (RBPsIn mammalian cells, RNA-binding proteins (RBPs) are major regulators of mRNA stability and translation. Some RBPs associate with RNA sequences that are widely present in mRNAs, such as the 5Ј cap structure (7-methyl-guanosine) or the 3Ј poly(A) tail. However, a distinct, albeit heterogeneous, group of mammalian RBPs associate with specific mRNA sequences (cis elements) frequently present in the 5Ј and 3Ј untranslated regions (UTRs) and effect changes in mRNA stability and translation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
167
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 188 publications
(183 citation statements)
references
References 66 publications
(80 reference statements)
16
167
0
Order By: Relevance
“…One interesting facet of this study is that it describes an example of one type of posttranscriptional regulator (a miRNA) controlling the expression of another type of posttranscriptional regulator (an RBP). Previous reports showed that some TTR-RBPs can modulate posttranscriptionally the expression of other TTR-RBPs (3,31); the present study provides a prominent example of a miRNA regulating a TTR-RBP. The fact that HuR enhances the stability of many target mRNAs raises an intriguing possibility for further consideration: if miR-519 is found to trigger the decay of a putative target mRNA, it is possible that the effect is indirect, should HuR be a stabilizing TTR-RBP for that particular mRNA.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…One interesting facet of this study is that it describes an example of one type of posttranscriptional regulator (a miRNA) controlling the expression of another type of posttranscriptional regulator (an RBP). Previous reports showed that some TTR-RBPs can modulate posttranscriptionally the expression of other TTR-RBPs (3,31); the present study provides a prominent example of a miRNA regulating a TTR-RBP. The fact that HuR enhances the stability of many target mRNAs raises an intriguing possibility for further consideration: if miR-519 is found to trigger the decay of a putative target mRNA, it is possible that the effect is indirect, should HuR be a stabilizing TTR-RBP for that particular mRNA.…”
Section: Discussionmentioning
confidence: 94%
“…Although many RBPs have housekeeping functions and associate with cellular transcripts, several RBPs have emerged that bind to specific subsets of mRNAs and play essential roles in controlling gene expression patterns in response to cell stimulation. These include a family of RBPs that modulate protein expression patterns in response to external factors by altering the cytoplasmic fate of target mRNAs, primarily by acting as translation and turnover regulatory (TTR)-RBPs (3,4). HuR is among the most prominent sequence-specific TTR-RBPs influencing the cellular response to stress agents, proliferative signals, immune triggers, and developmental cues (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Plant RBPs in the second clade showed strong homologies to T-cell-restricted intracellular antigen (TIA-1) and TIA-1-related protein (TIAR), both of which function as mRNA turnover and translation regulatory (TTR) RBPs (MazanMamczarz et al, 2006;Pullmann et al, 2007). TIA-1 and TIAR also are involved in signaling apoptotic cell death in mammalian systems (Kawakami et al, 1992;Taupin et al, 1995;Tian et al, 1991) and are important players in oxidative stress signaling (Abdelmohsen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on AUF1, KSRP, HuR, NF90, TIA-1 and TIAR found that each of these factors bind to their own mRNAs, indicating their auto-regulatory capacity, and that each may also regulate expression of one or more of the others. 39 Typical targets of the tandem zinc-finger protein, tristetraprolin (TTP), are mRNAs regulating tumor growth such as tumor necrosis factor (TNFα), cyclooxygenase 2 (COX-2), vascular endothelial growth factor (VEGF), interleukin 10 (IL-10) and immediate-early response 3 (Ier3). [40][41][42][43][44] TTP binds to AREs within the 3' UTR of these mRNAs and promotes their degradation.…”
Section: ' Utr Cis-acting Regulatory Elementsmentioning
confidence: 99%